Musical Memory: Audience Redintegration through Tembang Kenangan Performances at THR Sriwedari Solo - Widya Wardani, Galuh (Global Journal of Social Learning, 2025)
This study aims to examine how the process of redintegration occurs in the audience through the Tembang Kenangan performances held at Taman Hiburan Remaja Sriwedari (THR) Solo. The primary focus of this research is to explore how the music group D’Oldies, as one of the performers, can trigger the recollection of past events among the audience through nostalgic songs. Using a music psychology approach, particularly the concept of redintegration, this study seeks to delve deeper into the relationship between music, memory, and past life experiences that are reawakened through Tembang Kenangan. Redintegration refers to the process of retrieving memories or past events through specific cues or triggers, in this case, through music. This research employs a descriptive analytical method to describe how Tembang Kenangan music can serve as a reminder and the psychological process that occurs in the audience. The findings of this study are expected to contribute to the understanding of the relationship between music and memory, as well as how music can be used as a medium to recall and reflect on past life experiences.